Jazz dance a history of the roots and branches - Guarino, Lindsay; Oliver, Wendy (2014 Gainesville, Fl, 2014)
Unique in its focus on history rather than technique, Jazz Dance offers the only overview of trends and developments since 1960. Editors Lindsay Guarino and Wendy Oliver have assembled an array of seasoned practitioners and scholars who trace the numerous histories of jazz dance and examine various aspects of the field, including influences, training, race, aesthetics, international appeal, and its relationship to tap, rock, indie, black concert dance, and Latin dance. Featuring discussions of such dancers and choreographers as Bob Fosse and Katherine Dunham, as well as analyses of how the form's vocabulary differs from ballet, this complex and compelling history captures the very essence of jazz dance
Part I What is jazz dance -- Part II Jazz dance history -- Part III Master teachers and choreographers -- Part IV Related forms and styles -- Part V Perspectives on teaching and training -- Part VI Contemporary topics in jazz dance
Includes bibliographical references and index
Keywords: Jazz dance -- History; Dance -- History